Chemerin inhibits vascular calcification through ChemR23 and is associated with lower coronary calcium in chronic kidney disease. (7th July 2019) - Carracedo, M.; Witasp, A.; Qureshi, A. R.; Laguna‐Fernandez, A.; Brismar, T.; Stenvinkel, P.; Bäck, M.
Abstract: Background: Chemerin is an adipokine that signals through the G protein‐coupled receptor ChemR23 and is associated with inflammation, glucose homeostasis, lipid metabolism and renal function, all of which strongly influence cardiovascular risk. However, elevated chemerin provides a survival advantage in patients with chronic kidney disease (CKD), but how this relates to the cardiovascular phenotype is unknown. Objectives: The aim of the present study was to establish the association of chemerin with coronary calcification and to determine the effects of chemerin signalling, through ChemR23, in vascular smooth muscle cell (VSMC) calcification. Methods: Plasma chemerin was measured in 113 patients with CKD and 50 healthy controls. All patients underwent computed tomography to determine coronary artery calcium (CAC) score. VSMCs were isolated from wild‐type and ChemR23 knock‐out mice and treated with chemerin. Results: Multivariate analyses established creatinine, cholesterol, body mass index and tumour necrosis factor as significant confounders for circulating chemerin levels. Despite these positive associations with renal function, cardiometabolic risk factors and inflammation, chemerin was inversely associated with CAC both in an age‐ and sex‐adjusted analysis and in a multivariate analysis adjusting for the aforementioned confounders. In addition, circulating chemerin levels were associated with the calcification inhibitors matrix gla protein (MGP) and fetuin‐A. Finally, chemerin significantly reduced phosphate‐induced calcification and increased MGP expression in VSMCs, whereas chemerin was devoid of these effects in VSMCs lacking ChemR23. Conclusion: In conclusion, these results suggest that chemerin signalling through ChemR23 in VSMCs protects against vascular calcification in CKD. Abstract :